PENGARUH FINANCIAL DISTRESS DAN LEVERAGE TERHADAP TAX AVOIDANCE - Yusuf, Destira Zahra; Marliani, Nenda (Journal of Information System, Applied, Management, Accounting and Research, 2025)
This study was conducted to describe and examine the effect of financial distress and leverage on tax avoidance. The inconsistency of the results of previous studies is the basis for researchers to conduct research again. The sample in this study were 54 companies in the Energy sector of the Oil, Gas, and Coal sub-sector listed on the Indonesia Stock Exchange in 2019-2023. Research using descriptive and verification methods. The data analysis method uses multiple linear regression analysis using Eviews 9 software. The results of the study prove that: (1) financial distress has a positive and significant effect on tax avoidance, (2) leverage has a positive, but insignificant effect on tax avoidance. When the company experiences financial difficulties, management is encouraged to engage in tax avoidance to maintain the company's survival. While leverage does not have a strong impact on tax avoidance.